Blockchain technology and auditor: a scientific mapping and future research paths - Rizki Oktavianto; Evy Nurhayati Sri Hardini; Blasius Erik Sibarani (Universitas Negeri Yogyakarta, 2026)
This study presents a systematic literature review (SLR) examining the relationship between blockchain technology implementation and the audit profession, particularly its implications for auditors’ roles and practices. The review follows established SLR guidelines and focuses on peer-reviewed English-language articles in the fields of business, management, and accounting published between 2018 and 2024. After a rigorous screening process, 50 articles were selected for in-depth bibliometric and qualitative content analysis. The findings identify three main streams of research: (1) the impact of blockchain technology on the audit profession; (2) the integration of blockchain into accounting and auditing practices; and (3) emerging issues and future challenges in blockchain-based auditing environments. This study contributes by synthesizing current knowledge and proposing directions for future research on blockchain and auditing.